Retrograde Use of Frontrunner Catheter in Superficial Femoral Artery for Flushing Long Segment Occlusions Involving Distal Common Femoral Artery - Chavarria, Nelson (Ann Vasc Dis, 2017)
We present the case of an 81-year-old female with flush occlusion of the superficial femoral artery (SFA) and percutaneous transluminal angioplasty. Initially, the antegrade approach failed due to flush occlusion without stump. Hard, round surfaced, calcific, and eccentric plaque of the ostium of SFA was also present, which involved distal common femoral artery (CFA). Thus, we successfully used a Frontrunner catheter for retrograde reentry at the lower position of the CFA. Various treatment strategies involving Frontrunner and atherectomy devices could make percutaneous procedures possible in femoropopliteal occlusive disease, involving the CFA.